Molecular identification of Gracilaria species (Gracilariales, Rhodophyta) obtained from the South Coast of Java Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Meinita MDN, Akromah N, Andriyani N, Setijanto, Harwanto D, Liu T. 2021. Molecular identification of Gracilaria species (Gracilariales, Rhodophyta) obtained from the South Coast of Java Island, Indonesia. Biodiversitas 22: 3046-3056. The study of seaweeds diversity and species identification is an important component of marine resource management. However, seaweed identification based on morphological characteristics has several limitations. Besides, DNA barcodes or the partial sequences of cytochrome c oxidase I (COX1) have been proved to identify seaweeds at the species level. To date, Gracilaria species molecular diversity has not been studied in the South Coast of Java Island. Hence, this study aimed to identify the Gracilaria spp. obtained from 6 different beaches along the South Coast of Java, based on the COX1 gene. COX1 gene utilization for identifying and observing the genetic diversity, both intraspecific (genetic variation within species) and interspecific (variations between species) of Gracilaria species in this study has produced good results. A total of 13 seaweed samples collected from beaches in this study were identified as Gracilaria salicornia, G. edulis, G. firma, and G. textorii. The results of genetic diversity analysis conducted using the COX1 gene showed the intraspecific diversity of G. edulis obtained from the beaches of Kondang Merak, Kukup, Nusakambangan, and Karapyak was included in the moderate diversity category. Also, the intraspecific diversity of G. salicornia obtained from the beaches of Kondang Merak, Kukup, and Nusakambangan was included in the moderate diversity category, while the intraspecific diversity of G. textorii from Menganti and Karapyak Beach had no diversity.